The influence of instagram, tiktok travel influencers and city branding on the decision to choose a tourist destination ( case study on @backpackertampan in bali ) - Melati, Ni Luh Putu Kurniayu; Fathorrahman, Fathorrahman; Pradiani, Theresia (Institut Pariwisata dan Bisnis Internasional, 2022)
Tourism is the attraction of a country or a tourist destination that can encourage tourists to visit. The decision to visit tourists is influenced by pull factors that come from the destination and push factors that encourage someone to travel. The role of internet plays an important role in the pattern of searching for travel information and the flow of choosing tourist destinations. In this case, Instagram and TikTok as the most popular social media are used which display photos and videos that are used as a reference for choosing tourist destinations. The existence of social media is supported by the presence of travel influencers, one of them is @backpackertampan. City branding is one of the important points in the image management of a destination which is closely related to how an image is built by travel influencers as a promotional media to introduce a tourist destination. The purpose of this study to measure (1) the impact of Instagram travel influencers on destination choice decisions, (2) the impact of Tiktok travel influencers on travel destination choice decisions, and (3) Impact of city branding on travel destination choice decisions, (4) Instagram travel influencers, Tiktok travel influencers, and city branding impacts on travel destination choice decisions. The focus of this research is on the followers of @backpackertampan in Bali. This type of research is a quantitative approach. The number of respondents to this survey was 100 respondents that followed @backpackertampan account in Bali and used a non-probability sampling technique called purposive sampling. As a result, all of the variables in this research have a significant positive effect on the choice of tourist destinations.